Productivity and profitability of wet season rice (Oryza sativa L.) as affected by varying levels of potassium humate foliar application in the Eastern coastal plain of Odisha - KUMARI, MEGHA; SAHOO, HEMANTA KUMAR; DWIBEDI, SANAT KUMAR; SINGH, TEEKAM; JENA, TWINKLE (Journal of Soil and Water Conservation, 2026)
A field experiment was conducted during the kharif season of 2021 at Odisha University of Agriculture and Technology, Bhubaneswar, to assess the influence of foliar spray of potassium humate on productivity and profitability of rice. The nine treatment combinations were tested in randomized complete block design (RCBD) with three replications. The results revealed that foliar application of potassium humate @ 3 g L-1 at tillering and PI stage (T7) recorded significantly higher yield attributes, grain and straw yield of rice over all treatments except T9 (potassium humate @ 4 g L-1 at tillering and PI stage) and T5 (potassium humate @ 2 g L-1 at tillering and PI stage). The highest profitability in terms of net return (` 55070 ha-1) and B: C (1.85) ratio were also observed with T7. Thus, foliar applications of potassium humate @ 3 g L-1 at the tillering and PI stage of rice were found to be more productive and profitable in the eastern coastal plain of Odisha.